2014
DOI: 10.1186/s12974-014-0150-2
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil contribution to spinal cord injury and repair

Abstract: Spinal cord injuries remain a critical issue in experimental and clinical research nowadays, and it is now well accepted that the immune response and subsequent inflammatory reactions are of significant importance in regulating the damage/repair balance after injury. The role of macrophages in such nervous system lesions now becomes clearer and their contribution in the wound healing process has been largely described in the last few years. Conversely, the contribution of neutrophils has traditionally been con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 97 publications
4
92
0
Order By: Relevance
“…As such, inhibition of neutrophil recruitment by neutralizing antibodies against the chemokine receptor CXCR2, which is for example activated by CINC1, ameliorated the disease in an animal model for atypical autoimmune encephalomyelitis [58]. Others investigated the role for neutrophil granulocytes during spinal cord injury and found mixed results; detrimental for tissue regeneration but also beneficial for promoting functional recovery [59] most likely depending on the timing during programing of the inflammatory process [60]. Interestingly, induction of neutropenia by a neutralizing antibody during severe LPS-induced systemic inflammation (i.p., 2.5mg/kg) revealed that such IL-1β-expressing neutrophils contribute to the induction and/or maintenance of depressionlike behaviours 48h after LPS-stimulation [56].…”
Section: Neutrophil Granulocytesmentioning
confidence: 99%
“…As such, inhibition of neutrophil recruitment by neutralizing antibodies against the chemokine receptor CXCR2, which is for example activated by CINC1, ameliorated the disease in an animal model for atypical autoimmune encephalomyelitis [58]. Others investigated the role for neutrophil granulocytes during spinal cord injury and found mixed results; detrimental for tissue regeneration but also beneficial for promoting functional recovery [59] most likely depending on the timing during programing of the inflammatory process [60]. Interestingly, induction of neutropenia by a neutralizing antibody during severe LPS-induced systemic inflammation (i.p., 2.5mg/kg) revealed that such IL-1β-expressing neutrophils contribute to the induction and/or maintenance of depressionlike behaviours 48h after LPS-stimulation [56].…”
Section: Neutrophil Granulocytesmentioning
confidence: 99%
“…Emerging evidence indicated that infiltrated neutrophils are the major source of the MMP-9 in SCI [15][16][17]. As the first inflammatory cells, neutrophils infiltrate the site of injury following traumatic CNS injury, and it peaks at 24 hrs after injury [18]. The infiltration of neutrophils is regulated by intercellular adhesion molecule-1 (ICAM-1), which expresses on endothelial cells, and high expression of ICAM-1 facilitates neutrophil adhesion and tissue infiltration [18].…”
Section: Introductionmentioning
confidence: 99%
“…As the first inflammatory cells, neutrophils infiltrate the site of injury following traumatic CNS injury, and it peaks at 24 hrs after injury [18]. The infiltration of neutrophils is regulated by intercellular adhesion molecule-1 (ICAM-1), which expresses on endothelial cells, and high expression of ICAM-1 facilitates neutrophil adhesion and tissue infiltration [18]. The infiltrated neutrophils accumulates in the inflammatory core of a tissue lesion to secret MMPs, which are oxidative and tissue-degrading enzymes [19].…”
Section: Introductionmentioning
confidence: 99%
“…Similar other studies, our data reveal that neutrophils are needed for encouraging functional recovery after spinal cord damage. They are initial inflammatory cells which appear at the lesion site and act by different mechanisms, such as releasing angiogenic factors, to induce inflammation-mediated tissue remodeling (29,30). We did not find any studies that investigate effects of B. serrata extract on the neuronal cells in traumatic SCI.…”
Section: Discussionmentioning
confidence: 91%